Hibridnost pravnega normiranja v Evropski uniji: Pravni in institucionalni vidiki uporabe mehkega prava in pojav hibridnih pravnih področij - Rošic Feguš, Verena (2023)
Hibridnost pravnega normiranja v Evropski uniji: Legal and Institutional Aspects of Use of Soft Law and the Existence of Hybrid Legal Fields. Normative environment of the EU has become a dynamic regulatory framework where legal acts of diverse normative nature are gaining importance and classical method of legislation despite remaining central is no longer exclusive for legal regulation. Due to shadow of hierarchy offered to soft law, when the »request« of soft law is unsuccessful, »voluntary must« and creative law-creation are formed: in specific circumstances soft law inter alia uses means of execution identical to means of execution of hard law; at the end the softness of law is therefore irrelevant. After empirical research of three legal fields the book offers conclusions on hybridity of legal regulation in the EU, where coexistence of soft and hard law creates hybrid legal fields, on which soft law is variable preconditioned by political conflict and contingent on distinctive criteria of EU's competence, as well as it proposes establishment of minimal procedural standards to ensure democratic legitimation.
Keywords: normative environment of the EU; soft law; hybridity; complementarity; minimal procedural standards